Ako ang tunay na Maya a reception study on kasambahays' identification with Maya Dela Rosa of "Be Careful with my Heart" - Gellor, Sarah Lois Cedula 1991- (2014)
"This research examines the response and identification of kasambahays or domestic helpers to Maya Dela Rosa, the nanny character in the phenomenal daytime program Be Careful With My Heart. compared to the usual representation of domestic helpers in television as oppressed, unintelligent and opportunistic (Genota,2012), Maya stands out by being represented positively: optimistic and successful in terms of career, love and family. Maya is also different from domestic helpers in real life who are usually invisible and abused (Sayres,2005). Identification in this research is defined as an imaginative process where the viewer takes on the identity of a media character and experiences the events of the story in the character's shoes (Cohen, 2001).Other responses like parasocial interaction, liking or disliking, similarity and differences, and imitation were also studied in this thesis. Using qualitative interviews to a sample size of five kasambahays working in Metropolitan Manila, the researcher discovered that respondents see Maya positively and admire her character. However, the respondents did not experience identification with her, but instead aspired to be like Maya and wished for a fairytale life like hers."